Music induces universal emotion-related psychophysiological responses: comparing Canadian listeners to Congolese Pygmies - Egermann, Hauke; Fernando, Nathalie; Chuen, Lorraine; McAdams, Stephen (Frontiers in Psychology, 2015)
Subjective and psychophysiological emotional responses to music from two different cultures were compared within these two cultures. Two identical experiments were conducted: the first in the Congolese rainforest with an isolated population of Mbenzélé Pygmies without any exposure to Western music and culture, the second with a group of Western music listeners, with no experience with Congolese music. Forty Pygmies and 40 Canadians listened in pairs to 19 music excerpts of 29 to 99 seconds in duration in random order (8 from the Pygmy population and 11 Western instrumental excerpts). For both groups, emotion components were continuously measured: subjective feeling (using a two- dimensional valence and arousal rating interface), peripheral physiological activation, and facial expression. While Pygmy music was rated as positive and arousing by Pygmies, ratings of Western music by Westerners covered the range from arousing to calming and from positive to negative. Comparing psychophysiological responses to emotional qualities of Pygmy music across participant groups showed no similarities. However, Western stimuli, rated as high and low arousing by Canadians, created similar responses in both participant groups (with high arousal associated with increases in subjective and physiological activation). Several low-level acoustical features of the music presented (tempo, pitch, and timbre) were shown to affect subjective and physiological arousal similarly in both cultures. Results suggest that while the subjective dimension of emotional valence might be mediated by cultural learning, changes in arousal might involve a more basic, universal response to low-level acoustical characteristics of music.